Different Neural Responses for Unfinished Sentence as a Conventional Indirect Refusal Between Native and Non-native Speakers: An Event-Related Potential Study - Wang, Min; Tokimoto, Shingo; Song, Ge; Ueno, Takashi; Koizumi, Masatoshi; Kiyama, Sachiko (Frontiers in Psychology, 2022)
Refusal is considered a face-threatening act (FTA), since it contradicts the inviter’s expectations. In the case of Japanese, native speakers (NS) are known to prefer to leave sentences unfinished for a conventional indirect refusal. Successful comprehension of this indirect refusal depends on whether the addressee is fully conventionalized to the preference for syntactic unfinishedness so that they can identify the true intention of the refusal. Then, non-native speakers (NNS) who are not fully accustomed to the convention may be confused by the indirect style. In the present study, we used event-related potentials (ERPs) of electroencephalography in an attempt to differentiate the neural substrates for perceiving unfinished sentences in a conventionalized indirect refusal as an FTA between NS and NNS, in terms of the unfinishedness and indirectness of the critical sentence. In addition, we examined the effects of individual differences in mentalization, which refers to the ability to infer the mental states of others. We found several different ERP effects for these refusals between NS and NNS. NNS induced stronger P600 effects for the unfinishedness of the refusal sentences, suggesting their perceived syntactic anomaly. This was not evoked in NS. NNS also revealed the effects of N400 and P300 for the indirectness of refusal sentences, which can be interpreted as their increased processing load for pragmatic processing in the inexperienced contextual flow. We further found that the NNS’s individual mentalizing ability correlates with the effect of N400 mentioned above, indicating that lower mentalizers evoke higher N400 for indirect refusal. NS, on the contrary, did not yield these effects. Instead, they evoked earlier ERPs of early posterior negativity (EPN) and P200, both of which are known as indices of emotional processing, for finished sentences of refusal than for unfinished ones. We interpreted these effects as a NS’s dispreference for finished sentences to realize an FTA, given that unfinished sentences are considered more polite and conventionalized in Japanese social encounters. Overall, these findings provide evidence that a syntactic property inherent in a cultural convention as well as individual mentalizing ability plays an important role in understanding an indirect speech act of face-threatening refusal.